Periconceptional Folic Acid Supplementation and Newborn Birth Weights - Lin, Jing; Wang, Cheng; Li, Sisi; Zhang, Jie; Jin, Lei; Tong, Mingkun; Meng, Wenying; Ren, Aiguo; Chen, Lei; Jin, Lei (Frontiers in Pediatrics, 2022)
Evidence that periconceptional folic acid supplementation prevents neural tube defects has stimulated research on the relationship between maternal folic acid supplementation and newborn birth weights. However, the relationship between maternal folic acid supplementation and the birth weights of offspring remains inconclusive. Data on 31,107 births from 2015-2018 were extracted from the population-based prenatal health care system in a district of Beijing, China. Generalized linear and logistic regression models were used to evaluate the association between maternal periconceptional folic acid supplementation and birth weights or with risk of small for gestational week age (SGA) and large for gestational week age (LGA). Compared with newborns whose mothers did not use any folic acid supplements, the newborns with maternal periconceptional folic acid supplementation had similar median birth weight but had a lower risk of SGA [adjusted odds ratio (aOR)=0.81, (95% CI: 0.68-0.97)], however newborns born to mothers who took multiple micronutrients with folic acid (MMFA) with high compliance had a 25.26g (95% CI: 6.16, 44.36) higher median birth weight. Periconceptional women took folic acid only (FAO) (aOR=0.83; 95%CI: 0.67-1.01) or MMFA (aOR=0.74; 95%CI: 0.60-0.91) with high compliance decreased the risk of SGA. However , periconceptional folic acid supplementation has no impact on the risk of LGA (P<0.05). Periconceptional FAO or MMFA supplementation reduces the risk of SGA, with MMFA having a stronger effect than FAO. Periconceptional folic acid supplementation has no impact on the average birth weight and the risk of LGA, but the high compliance of MMFA supplementation increases the average birth weight.